Positron Emission Tomography-Guided Treatment in Early-Stage Favorable Hodgkin Lymphoma: Final Results of the International, Randomized Phase III HD16 Trial by the German Hodgkin Study Group - Fuchs, Michael; Goergen, Helen; Kobe, Carsten; Kuhnert, Georg; Lohri, Andreas; Greil, Richard; Sasse, Stephanie; Topp, Max S.; Schäfer, Erhardt; Hertenstein, Bernd; Soekler, Martin; Vogelhuber, Martin; et al. (Journal of Clinical Oncology, 2019)
PURPOSE: Combined-modality treatment (CMT) with 2× ABVD (doxorubicin, bleomycin, vinblastine, and dacarbazine) and small-field radiotherapy is standard of care for patients with early-stage favorable Hodgkin lymphoma (HL). However, the role of radiotherapy has been challenged. Positron emission tomography (PET) after 2× ABVD (PET-2) might help to predict individual outcomes and guide treatment. METHODS: Between November 2009 and December 2015, we recruited patients age 18 to 75 years with newly diagnosed, early-stage favorable HL for this international randomized phase III trial. Patients were assigned to standard CMT of 2× ABVD and 20-Gy involved-field radiotherapy or PET-guided treatment, omitting involved-field radiotherapy after negative PET-2 (Deauville score < 3). Primary objectives were to exclude inferiority of 10% or more in 5-year progression-free survival (PFS) of ABVD alone compared with CMT in a per-protocol analysis among PET-2-negative patients (noninferiority margin for hazard ratio, 3.01) and to confirm PET-2 positivity (Deauville score ≥ 3) as a risk factor for PFS among CMT-treated patients. RESULTS: We enrolled 1,150 patients. Median follow-up was 45 months. Among 628 PET-2-negative, per-protocol-treated patients, 5-year PFS was 93.4% (95% CI, 90.4% to 96.5%) with CMT and 86.1% (95% CI, 81.4% to 90.9%) with ABVD (difference 7.3% [95% CI, 1.6% to 13.0%]; hazard ratio, 1.78 [95% CI, 1.02 to 3.12]). Five-year overall survival was 98.1% (95% CI, 96.5% to 99.8%) with CMT and 98.4% (95% CI, 96.5% to 100.0%) with ABVD. Among 693 patients who were assigned to CMT, 5-year PFS was 93.2% (95% CI, 90.2% to 96.2%) among PET-2-negative patients and 88.4% (95% CI, 84.2% to 92.6%) in PET-2-positive patients (P = .047). When using the more common liver cutoff (Deauville score, 4) for PET-2 positivity, the difference was more pronounced (5-year PFS, 93.1% [95% CI, 90.7% to 95.5%] v 80.9% [95% CI, 72.2% to 89.7%]; P = .0011). CONCLUSION: In early-stage favorable HL, a positive PET after two cycles ABVD indicates a high risk for treatment failure, particularly when a Deauville score of 4 is used as a cutoff for positivity. In PET-2-negative patients, radiotherapy cannot be omitted from CMT without clinically relevant loss of tumor control.
CRIS-Team Scopus Importer:2019-11-08